Literature review on entrepreneurial self-efficacy and its role in project management success - Alsharabi O.M.N.; Daud S.; Jaaffar A.H. (Springer Science and Business Media Deutschland GmbH, 2025)
This review delves into the vital but often challenging realm of project management, emphasizing the significance of the human dimension, particularly Entrepreneurial Self-Efficacy (ESE). Investigating correlations between Project Management Success (PMS) dimensions and ESE, the review explores the influence of ESE on crucial variables like cost, time, quality, and business impact. Extending its focus to small and medium-sized enterprises (SMEs), the review addresses research gaps and advocates for future exploration of project managers? Entrepreneurial Self-efficacy (PM ESE). Conclusively, the study underscores project management?s critical role, urges the integration of the human dimension, and highlights ESE as a pivotal determinant, calling for comprehensive research to enhance our understanding of project management in contemporary organizational landscapes. ? The Author(s).